Immunosuppressants in modern approaches to treatment of inflammatory bowel diseases - O. B. Schukina; A. G. Kharitonov; A. M. Kharitidis; T. E. Ivashchenko; Yu. A. Nasykhova; T. V. Gabrusskaya; A. Yu. Baranovsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To characterize frequency of TPMT gene mutations in patients with inflammatory bowel diseases (IBD) with myelosuppression and to estimate value of these mutations in prognosis of myelosuppression development in patients receiving thiopurine treatment.Material and methods. From general register of IBD patients, those with bone marrow toxicity on a background of immunosuppressants in past history (n=21) were selected for assessment of TPMT gene allelic variants by polymerase chain reaction.Results. Only in one patient (4,7%) with Crohn's disease and leukopenia (3,85·109/l) and thrombocytopenia (80·109/l), developed in the remote terms (61 wks) after onset of azathioprin intake, TPMT*3A polymorphism has been revealed, as point mutations 460 G> A and 719A>G. In all other cases (20 patients) allelic variant TPMT*1 with normal enzyme production have been found.Conclusions. There is no need of study for genetic mutations before prescription of thiopurines, however application of effective methods of evaluation of prognosis of bone marrow toxicity development remains an actual issue. Careful control of laboratory parameters of myelosuppression during treatment by thiopurines is required. In case of intolerance or bone marrow toxicity at intake of thiopurines methotrexate should be prescribed.